Importance of Endocytosis for the Biological Activity of Cedar Virus Fusion Protein - Kerstin Fischer (Cells, 2020)
Endocytosis plays a particular role in the proteolytic activation of highly pathogenic henipaviruses Hendra (HeV) and Nipah virus (NiV) fusion (F) protein precursors. These proteins require endocytic uptake from the cell surface to be cleaved by cellular proteases within the endosomal compartment, followed by recycling to the plasma membrane for incorporation into budding virions or mediation of cell-cell fusion. This internalization largely depends on a tyrosine-based consensus motif for endocytosis present in the cytoplasmic tail of HeV and NiV F. Given the large number of tyrosine residues present in the F protein cytoplasmic domain of Cedar virus (CedV), a closely related but low pathogenic henipavirus, we aimed to investigate whether CedV F protein undergoes signal-mediated endocytosis from the cell surface controlled by tyrosine-based motifs present in its cytoplasmic tail and whether endocytosis is relevant for its biological activity. Therefore, tyrosine-based signals were mutated, and mutations were assessed for their effect on F cell surface expression, endocytosis, and biological activity. A membrane-proximal YXXΦ motif and a C-terminal di-tyrosine motif are of particular importance for cell surface expression and endocytosis rate. Furthermore, our data strongly indicate the pivotal role of endocytosis for the biological activity of the CedV F protein.